2010
DOI: 10.1387/ijdb.093009sr
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Stra6 and Rdh10 in the avian embryo and their contribution to the generation of retinoid signatures

Abstract: Two new components of the retinoic acid (RA) synthetic pathway, the cell surface receptor for retinol, Stra6, and the enzyme converting retinol into retinal, Rdh10, have recently been described. To understand how different tissues of the chick embryo generate different retinoid signatures, we describe the expression patterns of these two genes and ask whether they are altered by RA levels. We performed wholemount in situ hybridisation and altered RA levels by applying RA soaked beads and used vitamin A-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 51 publications
(65 reference statements)
0
28
0
Order By: Relevance
“…61), enzymes of the RA biosynthesis pathway appear to be largely absent from CNS (62). In mice, RALDH2 was not detected in the posterior neural tube, whereas RDH10 was detected only in the floor plate (19,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…61), enzymes of the RA biosynthesis pathway appear to be largely absent from CNS (62). In mice, RALDH2 was not detected in the posterior neural tube, whereas RDH10 was detected only in the floor plate (19,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…This model was also based on the notion of a feedback loop between RA levels and Rdh10 expression (14). Rdh10 expression has been analyzed in chicken and mouse but, in contrast to Xenopus, its expression is unaffected by excess RA or absence of RA in chicken (15) and is not altered in Raldh2 Fig. S9).…”
Section: Discussionmentioning
confidence: 99%
“…Marine fishes mainly use Ral and β-carotene as RA precursors (53), enzymes of the BCO family catalyzing β-carotene cleavage into Ral (4,5). Although the role of the Rdh10 homolog(s) remains to be established in zebrafish, recent studies demonstrated a function of RDH10 in early Xenopus development (14), and expression data suggested a conserved role in avian embryos (15). There may be a trend toward higher Rol/retinyl esters (versus Ral/carotenoids) stores in eggs from amphibian and amniote species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Xenopus laevis , rdh10 expression is suppressed by atRA ( 181 ), but in chick, RDH10 is not affected by the excess or absence of atRA ( 180 ). A more systematic analysis of atRA effect on the expression of retinol dehydrogenases and retinaldehyde dehydrogenases is needed to better understand the effect of vitamin A status on the conversion of retinol to retinaldehyde in different species.…”
Section: Downloaded Frommentioning
confidence: 99%